The legal nature of the regulatory decisions of the Supreme court of the Republic of Kazakhstan - Turegeldiyev, B.U.; Issayeva, A.Zh.; Nurutdinova, A.Zh. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The present аrticle is based on the study of the nature of the regulatory resolutions of the Supreme Court of the Republic of Kazakhstan on the legal platform, as well as in determining the place of normative decisions of the Supreme Court in the public consciousness at the present time and the contribution to the establishment of legality, the place in the categories of legal acts. The analysis of the contribution to the Judicial system and Common Law formation in the sequence of application of legality and legal standards are given, the results are criticized. In the legal field, the definition of the meaning of normative decisions of the Supreme Court and its constant practical application. This article seeks to assess the legal status, functions and consequences of normative decisions by Kazakhstan’s Supreme Court on legislation and law enforcement in Kazakhstan. Specifically, its study seeks to explore their specificities within Kazakhstan’s legal system as well as with relation to legislative bodies. This work has significant theoretical and practical importance, contributing to an enhanced understanding of legal regulation mechanisms in Kazakhstan as well as exploring how judicial practice influences legal norm formation. The focus of the present research lies on an examination of legislation, legal normative acts and judicial practice.